The Effect Of Adding Isolate Soy Protein And Porang Flour Towards Tilapia Sausage Organoleptic - Aslim, Fauzyah; Faridah, Anni; Kasmita, Kasmita; Holinesti, Rahmi (Universitas Negeri Padang, 2023)
This research was motivated by the use of fish as the main ingredient in making sausages which are still rarely found. Tilapia is one of the leading sources of animal protein in fisheries in Indonesia because of its easy cultivation. The addition of soy protein isolate and porang flour in this study is as a binder and sausage filler. The purpose of this research was to analyze the organoleptic properties of tilapia sausage with the addition of soy protein isolate and porang flour. This study used a Complete Randomized Design method (RAL) with 4 treatments and 3 repeats. The research data was obtained from organoleptic tests by 5 limited panelists in May 2023 at the Culinary Workshop of Padang State University. Data were analyzed using Analysis of Variance (ANAVA), if Fcount > Ftable then Duncan's Test was continued. The results showed that there was a significant influence on texture. While shape, color, odor and taste did not show a significant effect. Overall, the best results of this study were found in X2 treatment with the addition of soy protein isolate and porang flour 1: 1.